2014
DOI: 10.1007/s10551-014-2287-4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Choice Architecture on Sustainable Consumer Behavior: The Role of Guilt

Abstract: Companies often encourage consumers to engage in sustainable behaviors using their services in a more environmentally friendly or green way, such as reusing the towels in a hotel or replacing paper bank statements by electronic statements. Sometimes, the option of green service is implied as the default and consumers can opt-out, while in other cases consumers need to explicitly ask (opt-in) for switching to a green service. This research examines the effectiveness of choice architecture and particularly the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 59 publications
(85 reference statements)
2
73
1
Order By: Relevance
“…Prior research has shown that choosing utilitarian attributes can lead to less guilt, such as in the context of a trade-off with hedonic attributes (Kivetz and Simonson 2002), because choosing the former is the morally superior decision (Chitturi et al 2007). However, prior research in this journal (Steenhaut and Kenhove 2006;Theotokis and Manganari 2014) and elsewhere (Luchs, et al 2012;Peloza et al 2012;Tangney et al 2007) has shown that not choosing greater sustainability can also lead to feelings of guilt. Thus, choosing in favor of utilitarian value can lead to either less guilt or more guilt depending on what is being traded off.…”
Section: Trading-off Sustainability and Utilitarian Valuementioning
confidence: 94%
See 2 more Smart Citations
“…Prior research has shown that choosing utilitarian attributes can lead to less guilt, such as in the context of a trade-off with hedonic attributes (Kivetz and Simonson 2002), because choosing the former is the morally superior decision (Chitturi et al 2007). However, prior research in this journal (Steenhaut and Kenhove 2006;Theotokis and Manganari 2014) and elsewhere (Luchs, et al 2012;Peloza et al 2012;Tangney et al 2007) has shown that not choosing greater sustainability can also lead to feelings of guilt. Thus, choosing in favor of utilitarian value can lead to either less guilt or more guilt depending on what is being traded off.…”
Section: Trading-off Sustainability and Utilitarian Valuementioning
confidence: 94%
“…First, Study 1A employed a forced choice scenario. It is likely that some participants would not have chosen either of the options and that this might have influenced the results, especially given that the choice task itself and the way the options are structured is likely to have evoked emotions (Luce et al 1997;Theotokis and Manganari 2014). Second, the context of Study 1A was limited to kitchen blenders, which is a relatively utilitarian product category.…”
Section: The Effect Of Consumers' Attitude Towards Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Results reveal that hotel customers responded more favourably to a message that informed them that other hotel customers reused their towels compared to a message that informed them about the environmental value of towel reuse programmes (Goldstein, Cialdini, & Griskevicius, 2008). Theotokis and Manganari (2014) investigated the role of defaults in nudging consumers to reuse hotel towels and showed that the opt-out default policy engaged higher participation rates compared to the opt-in. Accordingly, Shang et al (2010) argued that placing the hotel logo in the notification card of a towel reuse programme, and underlying that the savings will be donated to charity, increases consumers' perceptions about the hotel's altruistic motivation and their willingness to participate.…”
Section: The Effectiveness Of Communicating Green Initiativesmentioning
confidence: 99%
“…(Emmett 2014). This may be particularly worrying when certain green nudges induce feelings of shame or guilt on the part of the nudges -which may be the case with nudges involving social status competition (see above, section 4.3) or even with green defaults whose behavioral impact may be due to feelings of guilt (Theotokis and Manganari 2014). 68 Green nudges risk representing an individualistic approach 67 Analogous reasoning applies to potential redistributive impact of different kinds of nudges: For instance, nudges aimed at 'System 1' (graphic warnings, say) may have a larger impact on intuitively thinking consumers, as compared to more analytically thinking peers.…”
mentioning
confidence: 99%